A Nap és a Hold - Dömötör, Péter (Hungary; MTVA, 2009)
The film leads us through the lives of two women, to the place where we meet them, Bodo. 98 percent of the population of Bódvalenke is Roma, almost everyone is unemployed. There is no walkway on the farm, gas heating, and water is also being transported from hundreds of meters to their homes by the people living there. However, with an exciting and unique program, people seem to be hoping to have jobs and a better life.
Verzio Film Festival Submission
Keywords: Documentary films